Rapid and sensitive detection of Haemophilus influenzae using multiple cross displacement amplification combined with CRISPR-Cas12a-based biosensing system - Xinbei Jia; Wenjian Xu; Fei Xiao; Nan Jia; Xiaolan Huang; Yiqin Zhang; Juan Zhou; Yi Wang; Jun Tai (Heliyon)
Haemophilus influenzae (H. influenzae, Hi) is an opportunistic bacterium that colonizes the upper respiratory tract of humans and frequently causes meningitis, pneumonia, sepsis, and other severe infections in children. Early and accurate detection of H. influenzae is essential for effective diagnosis and treatment. In this study, we established a novel diagnostic method by integrating the CRISPR-Cas12a detection platform with multiple cross-displacement amplification (MCDA), termed the Hi-MCDA-CRISPR assay. This method offers an efficient and highly precise diagnostic tool for the identification of H. influenzae. In the Hi-MCDA-CRISPR system, the outer membrane protein (OMP) P6 of H. influenzae was pre-amplified using the MCDA assay. The CRISPR-Cas12a-gRNA complex specifically recognized and bound to the amplified gene, forming a ternary complex that triggered the nonspecific trans-cleavage of the Cas12a effector, which subsequently degraded the fluorescent-quenched single-stranded DNA (ssDNA) probes, resulting in the emission of detectable fluorescent signals. After optimizing the reaction conditions, the Hi-MCDA-CRISPR assay proved capable of completing H. influenzae detection within 45 min, including a 40 min MCDA pre-amplification at 62 °C and a 5 min CRISPR-Cas12a cleavage at 37 °C. The assay was able to detect H. influenzae genomic DNA at concentrations as low as 50 fg and showed no cross-reactivity with non-H. influenzae pathogens. Furthermore, the Hi-MCDA-CRISPR assay successfully analyzed 65 clinical sputum samples. These findings suggest that the Hi-MCDA-CRISPR assay is a promising new detection tool for the rapid and reliable diagnosis of H. influenzae infection.